AUDIT SISTEM INFORMASI AKADEMIK MENGGUNAKAN METODE COBIT 5 - Tri Rahayu; Nurhafifah Matondang; Bayu Hananto (Universitas Negeri Padang, 2020)
The purpose of this study is to measure the level of maturity and application of information technology performance in implementing the Academic Information System (SIAKAD) at the